استراتيجية العنونة في المقامات الباقوزية لأبي الرتيم الشرشماني للكاتب محمود عياشي - بومعزة, نوال; سيد, مبروكة; معيزة, جمعة (University of Eloued جامعة الوادي, 2024)
يعد علم العنونة من أهم القضايا النقدية المعاصرة التي تعنى بالعنوان، حيث اسهم الدرس السيميائي في بروزه لمكانته الهامة لانفتاحه على النص، فهو أولى العتبات النصية للولوج لعوالم النص الخفية ذات الرمزية العالية؛ ولفك شفراتها لجأ النقاد لاستراتيجية قائمة على قراءة منهجية مفصلة لكل عنوان أدبي مشكلة نص موازي جاهز للحفر والتنقيب والتعقيب فيه من خلال قراءة نقدية واعية سيميائية لأي عنوان مهما كان جنسه، وفن المقامة هو جنس أدبي اعتنى بالعنوان قديما وحديثا لما تشكله المقامة المعاصرة من أهمية في معالجة العديد من القضايا الاجتماعية بصورة ساخرة أو ناقدة أو ثائرة على مجريات العصر الحالي. The study of titling is one of the most important contemporary critical issues concerned with titles. The semiotic study has contributed to highlighting its significance due to its openness to the text. The title is the first textual threshold to access the hidden worlds of the text with high symbolism. To decode its codes, I resorted to a strategy based on a detailed methodological reading of each literary title, forming a parallel text ready for excavation, investigation, and critique through a conscious semiotic critical reading of any title, regardless of its genre. The art of Maqama is a literary genre that has paid attention to titles both in the past and the present, as contemporary Maqama holds significant importance in addressing various social issues in a satirical, critical, or rebellious manner against the current events of our time.
مقاربة سيميائية
818/001
Keywords: العنونة، المقامات الباقوزية، أبي الرتيم الشرشماني، محمود عياشي.; Al-Announa; Al-Maqamat Al-Baquziyya; Abu Al-Rateem Al-Sharshmani; Mahmoud Ayashi.